Fournier’s gangrene in females: A rare entity - Kumar, A Prem; Gopalakrishnan Nair, Sandesh (Indian Journal of Case Reports, 2021)
Fournier’s gangrene is a form of necrotizing fascitis with abrupt onset of rapidly fulminating genital gangrene of idiopathic origin and gangrene up to deep fascia. It occurs usually in patients with urogenital infections and comorbidities such as diabetes, immunosuppression, or even trauma. Here, we present one such case of an 86-year-old female presenting with a history of pain and purulent discharge from the perianal region for 5 days. On examination, a wound of 20 × 15 cm perineal region extending up to the gluteal region posteriorly and labia majora anteriorly. The patient was planned for debridement under spinal anesthesia on an emergency basis followed by regular dressing and antibiotic therapy. The peri-operative period was uneventful. Along with surgical management, the patient was managed medically by control of sugars, treating sepsis with appropriate antibiotics. The patient recovered from sepsis, and the wound showed granulation tissue after 1 week of serial debridement. The wound was closed with a skin graft at a later date. Fournier’s gangrene should be kept as a differential diagnosis in females with perineal abscesses or necrotizing fascitis in females.